General Dentist's knowledge in determining radiodiagnosis of lucent lesions through panoramic radiography: Study descriptive - Rahmadona, Suci; Epsilawati, Lusi; Damayanti, Merry Annisa; Jasrin, Tadeus Arufan; Susilawati, Sri; Zakiawati, Dewi (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACT Introduction: Radiology in dentistry plays an important role in diagnosis and treatment planning through radiographic examinations, such as panoramic radiography which provides a broad view of the bone and tooth structure. Mistakes in radiographic interpretation can lead to misdiagnosis, as shown by previous study which found a high percentage of misdiagnosis by practitioners. The aim of this study was to determine whether general dentists were able to interpret properly and correctly. Methods: This type of research was descriptive with a convenience sampling technique. The study was conducted on 96 general dentists using an instrument in the form of a questionnaire with 15 questions. Results: Based on the distribution of respondents, the majority were women domiciled outside the city of Bandung, most of whom worked in independent clinics (24,8%) and hospitals (21,4%). A total of 57 respondents (59,4%) were at the level of knowledge with a good category, then 36 people (37,5%) were in the sufficient category, and 3 people (3,1%) were in the less category; (4) Conclusions: The level of knowledge of general dentists in identifying the characteristics of lucent lesions is classified as good, but the ability to determine radiodiagnosis and differential radiodiagnosis is still lacking. Overall, the results of the study showed that the level of general dentists’ knowledge is categorized as adequate, with an average score of 10,8.KEY WORDS: Knowledge, radiodiagnosis, general dentist, lucent lesions, panoramic radiography Pengetahuan dokter gigi umum dalam menentukan radiodiagnosis lesi lusen melalui radiografi panoramik: deskriptif kualitatifABSTRAK Pendahuluan: Ilmu radiologi dalam kedokteran gigi berperan penting dalam diagnosis dan perencanaan perawatan melalui pemeriksaan radiografi, seperti radiografi panoramik yang memberikan gambaran luas struktur tulang dan gigi. Kesalahan dalam interpretasi radiografi dapat menyebabkan diagnosis yang keliru, sebagaimana ditunjukkan oleh peneliti sebelumnya yang menemukan persentase kesalahan diagnosis oleh praktisi cukup tinggi. Tujuan penelitian ini untuk mengetahui apakah dokter gigi umum sudah dapat melakukan interpretasi dengan baik dan benar. Metode: Jenis penelitian deskriptif dengan teknik pengambilan sampel convenience sampling. Penelitian dilakukan pada 96 dokter gigi umum menggunakan instrumen berupa kuesioner dengan 15 butir pertanyaan. Hasil: Berdasarkan distribusi responden, mayoritasnya merupakan perempuan dengan domisili di luar Kota Bandung yang sebagian besarnya bekerja pada klinik mandiri (24,8%) dan rumah sakit (21,4%). Sebanyak 57 responden (59,4%) berada pada tingkat pengetahuan dengan kategori baik lalu sebanyak 36 orang (37,5%) dengan kategori cukup, serta 3 orang (3,1%) dengan kategori kurang. Simpulan: Tingkat pengetahuan dokter gigi umum dalam mengidentifikasi karakteristik lesi lusen tergolong baik, tetapi kemampuan dalam menentukan radiodiagnosis dan radiagnosis banding masih kurang. Secara keseluruhan, hasil penelitian menunjukkan bahwa tingkat pengetahuan dokter gigi umum dikategorikan cukup dengan rerata perolehan nilai berada pada 10,8. KATA KUNCI: Pengetahuan, radiodiagnosis, dokter gigi umum, lesi lusen, radiografi panoramik